The Shroud: Ways Adolescents Manage Living With Parental Chronic Pain. Issue 4 (22nd May 2013) - Umberger, Wendy; Martsolf, Donna; Jacobson, Ann; Risko, Judy; Patterson, Mary; Calabro, Mary
Abstract Purpose The purpose of this article is to describe a substantive theory that details how adolescents manage living with a parent experiencing chronic noncancer pain (CNCP). Design Grounded theory methods were used to recruit 30 young adults, ages 18 through 21 years, from community settings. Methods During open‐ended interviews, participants were asked to look back on their adolescence and talk about how they managed living with parental chronic pain. Interview transcripts and field notes were analyzed using constant comparative methods. Findings Participants who lived with heavily shrouded parents (a) endured hardships; (b) distanced themselves; (c) lamented losses; and (d) held back on revealing their authentic selves. Those who lived with minimally shrouded parents (a) received nurturance and parenting; (b) empathized with their parents' pain situations; (c) lamented losses; and (d) revealed to their parents how parental pain affected them. Participants who connected with significant others "filled the gaps" created by parental pain disability, while those who did not connect with significant others "cooped up" their thoughts, feelings, and needs. Conclusions Findings shed light on psychosocial processes and behavior within families experiencing CNCP and serve as the basis for the development of personalized family interventions. Clinical Relevance Nursing interventions should focus on helping adolescents and parents build interpersonal relationship and communication skills. Aggressive diagnosis and treatment of mood disturbance in the parent with CNCP should be part of a holistic treatment plan.